(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
The article deals with the problem of semantic tagging of dialect words in Uzbek language as one of the tasks of improving the description of dialect words in the requirements of the time and in the explanatory dictionaries of the Uzbek language.